1973
DOI: 10.1104/pp.52.5.422
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Chlorophyll and Chlorogenic Acid Content in Tobacco Leaves

Abstract: A positive correlation (r = 0.75, P < 0.01) was obtained between chlorophyll and chlorogenic acid content in the seedling leaves of burley and dark tobaccos. The dark tobaccos contained significantly higher concentrations of both constituents than the burleys. Such a correlation also occurred in a cytoplasmic mutant of chlorophyll-variegated tobacco when the green and yellow laminae were compared. In addition, the activity of phenylalanine ammonia-lyase and polyphenol. (25,26). Biosynthesis of chlorogenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Specific identified metabolites included Chlorogenic acid (CGA) which was found to be associated with photosynthesis (positive), growth rate (negative), and biomass (negative). CGA is a highly abundant compound and has been demonstrated to have important roles in multiple plant organs including leaves (Sheen, 1973 ; Mondolot et al, 2006 ; Clé et al, 2008 ; Leiss et al, 2009 ), roots, and root hairs, (Narukawa et al, 2009 ; Franklin and Dias, 2011 ), and has roles in diverse processes such as wound response (Ramamurthy et al, 1992 ; Campos-Vargas and Saltveit, 2002 ) and cell-wall building (Aerts and Baumann, 1994 ; Mondolot et al, 2006 ). In our study, three CGA isomers were identified in leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Specific identified metabolites included Chlorogenic acid (CGA) which was found to be associated with photosynthesis (positive), growth rate (negative), and biomass (negative). CGA is a highly abundant compound and has been demonstrated to have important roles in multiple plant organs including leaves (Sheen, 1973 ; Mondolot et al, 2006 ; Clé et al, 2008 ; Leiss et al, 2009 ), roots, and root hairs, (Narukawa et al, 2009 ; Franklin and Dias, 2011 ), and has roles in diverse processes such as wound response (Ramamurthy et al, 1992 ; Campos-Vargas and Saltveit, 2002 ) and cell-wall building (Aerts and Baumann, 1994 ; Mondolot et al, 2006 ). In our study, three CGA isomers were identified in leaf extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a precursor of chlorogenic acid. The con-version of 14 C-L-phenylalanine into chlorogenic acid and the interference of phenylpyruvic acid on this conversion in tobacco leaf have been experimentally demonstrated (8). Therefore, the more chlorophyll synthesized, the greater the quantity of chlorogenic acid accumulated in the case of dark tobaccos bearing Yb 1 and Yb 2 genes.…”
Section: Resultsmentioning
confidence: 96%
“…Dark tobaccos are homozygously dominant for these loci, whereas Burleys are homozygously recessive. Quantitative variation of chlorophyll in tobacco affects the concentration of not only nitrogenous compounds but also polyphenols (8,9,10). The latter are one of the precursors of suspected tumor promotors in cigarette smoke (12).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that a positive correlation between chlorophyll and polyphenol content in tobacco leaves may be attributed to the conversion of L-phenylalanine to phenylpyruvate by a-aminolevulinic acid transaminase for mlorophyll biosynthesis. In this case, phenylpyruvate is a by-product and can be readily converted to cinnamic acid subsequently to polyphenols (10 reduced activities of• both oxidases as would be expected because of the high temperature (71 °C; 160 °F) during curing. Oxidase activities were higher in ripe green leaves of plants grown in the Burley tobacco region than those of plants in the flue-cured tobacco region.…”
Section: Methodsmentioning
confidence: 97%
“…These chemical and physical characteristics serve as criteria of leaf quality. A comparison of dark and Burley tobaccos showed a positive correlation between polyphenol and chlorophyll quantities in leaf lamina (10). Burley, as a chlorophyll-deficient mutant, differs from dark tobaccos by two recessive factors, ybt and yht (5), and is low in polyphenol content (12).…”
Section: Introductionmentioning
confidence: 99%